2022
DOI: 10.3389/fbioe.2022.868111
|View full text |Cite
|
Sign up to set email alerts
|

Silica Nanoparticle Acute Toxicity on Male Rattus norvegicus Domestica: Ethological Behavior, Hematological Disorders, Biochemical Analyses, Hepato-Renal Function, and Antioxidant-Immune Response

Abstract: With extensive production and various applications of silica nanoparticles (SiNPs), there is a controversy regarding the ecotoxicological impacts of SiNPs. Therefore, the current study was aimed to assess the acute toxicity of silica nanoparticles in male Rattus norvegicus domestica after 24 and 96 h. Hematological, serum biochemical, stress biomarker, and immune-antioxidant parameters were addressed. Chemical composition, crystal structure, and the particle shape and morphology of SiNPs were investigated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Although alkaline phosphatase enzyme is measured to detect liver or bone toxicity, a relation to liver disease has only been described when values are increased and not decreased. [50][51][52] Furthermore, there was no alteration of other biochemical parameters and the majority of blood populations analyzed remained stable compared to the untreated control. Only, a slight increase in hematocrit, as well as eosinophils, can be observed with exposure to both BML1 and BML2 nanoformulations, which had already been described by Askri et al with an increase in the number of red blood cells, hemoglobin, and eosinophils with low doses of iron oxide nanoparticles.…”
Section: Discussionmentioning
confidence: 89%
“…Although alkaline phosphatase enzyme is measured to detect liver or bone toxicity, a relation to liver disease has only been described when values are increased and not decreased. [50][51][52] Furthermore, there was no alteration of other biochemical parameters and the majority of blood populations analyzed remained stable compared to the untreated control. Only, a slight increase in hematocrit, as well as eosinophils, can be observed with exposure to both BML1 and BML2 nanoformulations, which had already been described by Askri et al with an increase in the number of red blood cells, hemoglobin, and eosinophils with low doses of iron oxide nanoparticles.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies supported this finding. For example, Almanaa et al [47] reported a noticeably increased cortisol level in male rats given SiNPs orally (125 mg/kg/d) for 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…These free radicals can initiate lipid peroxidation which brings about a rise in MDA levels 32 . In addition to the previously mentioned mechanism of tissue toxicity, numerous inflammatory mediators are released by various pathways, these inflammatory cytokines can magnify the toxicity 27,33 .…”
Section: Discussionmentioning
confidence: 99%